Functional Effects of the Buckwheat Iminosugar d‐Fagomine on Rats with Diet‐Induced Prediabetes. Issue 16 (1st August 2018) - Ramos‐Romero, Sara; Hereu, Mercè; Atienza, Lidia; Casas, Josefina; Taltavull, Núria; Romeu, Marta; Amézqueta, Susana; Dasilva, Gabriel; Medina, Isabel; Torres, Josep L.
Abstract : Scope: The goals of this work are to test ifd ‐fagomine, an iminosugar that reduces body weight gain, can delay the appearance of a fat‐induced prediabetic state in a rat model and to explore possible mechanisms behind its functional action. Methods and results: Wistar Kyoto rats were fed a high‐fat diet supplemented withd ‐fagomine (or not, for comparison) or a standard diet (controls) for 24 weeks. The variables measured were fasting blood glucose and insulin levels; glucose tolerance; diacylglycerols as intracellular mediators of insulin resistance in adipose tissue (AT), liver, and muscle; inflammation markers (plasma IL‐6 and leptin, and liver and AT histology markers); eicosanoids from arachidonic acid as lipid mediators of inflammation; and the populations of Bacteroidetes, Firmicutes, Enterobacteriales, and Bifidobacteriales in feces. It was found thatd ‐fagomine reduces fat‐induced impaired glucose tolerance, inflammation markers, and mediators (hepatic microgranulomas and lobular inflammation, plasma IL‐6, prostaglandin E2, and leukotriene B4 ) while attenuating the changes in the populations of Enterobacteriales and Bifidobacteriales. Conclusion: d ‐Fagomine delays the development of a fat‐induced prediabetic state in rats by reducing low‐grade inflammation. We suggest that the anti‐inflammatory effect ofd ‐fagomine may be linked to a reduction in fat‐induced overpopulation of minor gut bacteria. Abstract : The iminosugard ‐fagomine is a buckwheat component that reduces body weight gain and delays the development of prediabetes in rats fed a high‐fat diet. By measuring inflammation markers and lipid mediators of inflammation, it is found thatd ‐fagomine reduces fat‐induced low‐grade systemic inflammation.d ‐Fagomine partially counteracts the changes induced by the diet in the populations of gut Enterobacteria and Bifidobacteria. This research suggests effects ofd ‐fagomine on fat‐induced prediabetes, inflammation, and composition of gut microbiota may be connected.